Weight loss and quality of life in patients surviving 2 years after gastric cancer resection. Issue 7 (July 2017) - Climent, M.; Munarriz, M.; Blazeby, J.M.; Dorcaratto, D.; Ramón, J.M.; Carrera, M.J.; Fontane, L.; Grande, L.; Pera, M.
Abstract: Background: Malnutrition is common in patients undergoing gastric cancer resection, leading to weight loss, although little is known about how this impacts on health-related quality of life (HRQL). This study aimed to explore the association between HRQL and weight loss in patients 2 years after curative gastric cancer resection. Methods: Consecutive patients undergoing curative gastric cancer resection and surviving at least 2 years without disease recurrence were recruited. Patients completed the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and the specific module for gastric cancer (STO22) before and 2 years postoperatively and associations between HRQL scores and patients with and without ≥ 10% body weight loss (BWL) were examined. Results: A total of 76 patients were included, of whom 51 (67%) had BWL ≥10%. At 2 years postoperatively, BWL ≥10% was associated with deterioration of all functional aspects of quality of life, with persistent pain (21.6%), diarrhoea (13.7%) and nausea/vomiting (13.7%). By contrast, none of the patients with BWL <10% experienced severe nausea/vomiting, pain or diarrhoea. Conclusions: Disabling symptoms occurred more frequently in patients with ≥10% BWL than in those with <10% BWL, with a relevant negative impact on HRQL. A cause–effect relationship between weight loss and postoperative outcome remains unsolved.